Genetic Polymorphism of Aspergillus fumigatus in Clinical Samples from Patients with Invasive Aspergillosis: Investigation Using Multiple Typing Methods - Bertout, S. (American Society for Microbiology, 2001)
The genotypes of 52 strains of Aspergillus fumigatus isolated from 12 patients with invasive aspergillosis were investigated using three typing methods (random amplified polymorphic DNA, sequence-specific DNA polymorphism, and microsatellite polymorphism) combined with multilocus enzyme electrophoresis. Isolates were from patients hospitalized in three different geographic areas (Lyon, France; Grenoble, France; and Milan, Italy). In each case, the genetic polymorphism of several colonies (two to five) within the first respiratory clinical sample was studied. For the 52 isolates tested, random amplified polymorphic DNA identified 8 different genotypes, sequence-specific DNA polymorphism identified 9 different types, and microsatellite polymorphism identified 14 types. A combination of these results with multilocus enzyme electrophoresis study identified 25 different types within the sample studied. We identified 3 patients (of the 12 studied) who carried a single genotype; 6 patients were infected by two genotypes, 1 patient had four genotypes, while the last patient had five. A combination of typing methods provided better discrimination than the use of a single method. Typing methods revealed a population structure within each geographical site, suggesting that the epidemiology of A. fumigatus should be considered separately for each of these geographic areas. This study demonstrates the usefulness of combining several typing methods in reaching an understanding of the epidemiology of A. fumigatus and clarifies whether it is sufficient to type one isolate from each specimen to determine the strain involved in invasive aspergillosis.